Protein kinases C isozymes are differentially expressed in human breast carcinomas - Ali, Shadan (2009)
AIMS: The protein kinase C (PKC) family of enzymes has been implicated in cellular proliferation, differentiation, and apoptosis. However, the distribution of specific PKC isoforms with varying functions in normal and malignant human tissues remains to be determined. The objective of this study was to investigate the expression of certain PKC isoforms (α, βI, βII, ε) in human breast cancer specimens relative to adjacent uninvolved tissue (n = 24) and in the normal breast tissue obtained from patients undergoing reduction mammoplasty (n = 12). MAIN METHODS: Western blot analysis using PKC isoform specific antibodies was performed on tissue extracts from breast tumors, adjacent uninvolved tissues, and reduction mammoplasty tissues. KEY FINDINGS: Mean levels of cytosolic and membrane PKC-α, PKC-βI, and PKC-βII were significantly higher in the cancer specimens than in the adjacent uninvolved breast tissues (Wilcoxon signed-ranks test; P<0.05 for each, after adjustment for multiple comparisons). There was a notably higher mean level of membrane PKC-βII isozyme in Her-2 positive and in poorly differentiated tumors. No significant differences were observed when normal tissue adjacent to tumor was compared to breast tissue obtained from reduction mammoplasty specimens. SIGNIFICANCE: Higher level of PKC-α, PKC-βI, and PKC-βII in cancer specimens and higher level of PKC-βII in Her-2 positive tumors require further exploration of the intracellular pathways involving PKC-α and -β isoforms in breast cancer because both could be specific targets for the development of new therapies and for the prevention and treatment of this disease.